Capacidades dinâmicas a partir da gestão do conhecimento e da aprendizagem organizacional: em busca de desempenhos superiores - Gasparini, Liz Vanessa Lupi (2014)
The area of Strategic Planning seeks to understand how the company creates and maintains competitive advantage, considering factors external and internal constraints. Among these, the lines of thought related to the Resource Based View, the Knowledge Management and Organizational Learning, there are the Dynamic Capabilities, necessary for enterprises to integrate, build and reconfigure internal and external competencies to respond quickly to environmental changes: absorptive capacity related to knowledge; adaptive capacity, organizational learning; and innovation capacity related to innovation and market advantage. Still under development, this recent approach to strategic management is criticized for its weakness in guiding the development and management of capacity and organizational resources. This study proposes that the integration of knowledge management, generating absorptive capacity and organizational learning, generating adaptive capacity, can foster innovation and organizational performance, and can promote indirectly, mediated by innovation, superior organizational performance generated directly, characterizing the generation of innovation capacity; and that if this performance is superior to that of competitors, featuring competitive advantage. This argument has been translated into a model of hypotheses, to contribute to the research model of dynamic capabilities developed by Wang and Ahmed (2007) by detailing how dynamic capabilities can relate and generate differential performance and innovativeness. Results of the questionnaire developed and applied to CEOs of four plants manufacturing Mato Grosso biodiesel, and a national unit of a global corporation in the auto parts industry recognized for its innovativeness and its performance was compared qualitatively to illustrate the model proposed. The results of this study reinforced the proposition and hypotheses examined in a preliminary way. From the viewpoint of view of dynamic capabilities were related the effects of integration of knowledge management and organizational learning in innovation and organizational performance , and indicated how this integration can generate differential organizational performance and innovativeness.